Seed Dormancy and Soil Seed Bank of the Two Alpine Primula Species in the Hengduan Mountains of Southwest China - Peng, De-Li; Yang, Li-E; Yang, Juan; Li, Zhi-Min (Frontiers in Plant Science, 2021)
The timing of germination has long been recognized as a key seedling survival strategy for plants in highly variable alpine environments. Seed dormancy and germination mechanisms are important factors that determining the timing of germination. To gain an understanding of how these mechanisms help to synchronize the germination event to the beginning of the growing season in two of the most popular Primula species (P. secundiflora and P. sikkimensis) in the Hengduan Mountains, Southwest China, we explored their seed dormancy and germination characteristics in the laboratory and their soil seed bank type in the field. Germination was first tested using fresh seeds at two alternating temperatures (15/5 and 25/15°C) and five constant temperatures (5, 10, 15, 20, and 25°C) in light and dark, and again after dry after-ripening at room temperature for 6 months. Germination tests were also conducted at a range of temperatures (5–30, 25/15, and 15/5°C) in light and dark for seeds dry cold stored at 4°C for 4 years, after which they were incubated under the above-mentioned incubation conditions after different periods (4 and 8 weeks) of cold stratification. Base temperatures (Tb) and thermal times for 50% germination (θ50) were calculated. Seeds were buried at the collection site to test persistence in the soil for 5 years. Dry storage improved germination significantly, as compared with fresh seeds, suggesting after-ripening released physiological dormancy (PD); however, it was not sufficient to break dormancy. Cold stratification released PD completely after dry storage, increasing final germination, and widening the temperature range from medium to both high and low; moreover, the Tb and θ50 for germination decreased. Fresh seeds had a light requirement for germination, facilitating formation of a persistent soil seed bank. Although the requirement reduced during treatments for dormancy release or at lower alternating temperatures (15/5°C), a high proportion of viable seeds did not germinate even after 5 years of burial, showing that the seeds of these two species could cycle back to dormancy if the conditions were unfavorable during spring. In this study, fresh seeds of the two Primula species exhibited type 3 non-deep physiological dormancy and required light for germination. After dormancy release, they had a low thermal requirement for germination control, as well as rapid seed germination in spring and at/near the soil surface from the soil seed bank. Such dormancy and germination mechanisms reflect a germination strategy of these two Primula species, adapted to the same alpine environments.